A primer on mapping class groups (Princeton mathematical series) - Farb, Benson; Margalit, Dan (Princeton Mathematical Series, 2011)
The study of the mapping class group Mod(S) is a classical topic that is experiencing a renaissance. It lies at the juncture of geometry, topology, and group theory. This book explains as many important theorems, examples, and techniques as possible, quickly and directly, while at the same time giving full details and keeping the text nearly self-contained. The book is suitable for graduate students.